Hemosuccus Pancreaticus Associated with Segmental Arterial Mediolysis Successfully Treated by Transarterial Embolization - Naitoh, Itaru; Ando, Tomoaki; Shimohira, Masashi; Nakazawa, Takahiro; Hayashi, Kazuki; Okumura, Fumihiro; Miyabe, Katsuyuki; Yoshida, Michihiro; Togawa, Hiroyuki; Sasaki, Shigeru; Shibamoto, Yuta; Joh, Takashi (JOP. Journal of the Pancreas, 2010)
Context Hemosuccus pancreaticus, a rare cause of intermittent upper gastrointestinal bleeding, is usually caused by the rupture of an aneurysm associated with chronic pancreatitis. Segmental arterial mediolysis is a rare non-arteriosclerotic, non-inflammatory vascular disease characterized by vacuolization and lysis of the arterial smooth muscle cells. Segmental arterial mediolysis often causes intra-abdominal hemorrhage through aneurysm rupture. To our knowledge, hemosuccus pancreaticus associated with segmental arterial mediolysis has not previously been reported. Case report A 59-year-old man had suffered from recurrent episodes of epigastric pain and melena. Laboratory data showed mild anemia and an elevated serum amylase level. Upper gastrointestinal endoscopy revealed bloody pancreatic juice exuding from the papilla of Vater. There were no findings suggestive of chronic pancreatitis, such as pancreatic calcification, irregularity of the pancreatic duct and atrophy of the pancreas. Contrast-enhanced computed tomography revealed a large fusiform aneurysm of the middle-distal splenic artery, and dissection of the proximal splenic artery and celiac artery. Leakage of contrast medium from the aneurysm into the main pancreatic duct was also evident. Angiography clearly revealed a fusiform aneurysm of the splenic artery. This was managed successfully by transarterial coil embolization and the patient has subsequently shown no recurrence of epigastric pain or melena. Conclusion Segmental arterial mediolysis is a very rare cause of hemosuccus pancreaticus not associated with chronic pancreatitis. Transcatheter arterial embolization is useful for treatment of ruptured aneurysm associated with segmental arterial mediolysis. Image: 3D-CT angiography showing a leakage of contrast medium from a fusiform aneurysm of the middle-distal splenic artery.